Subsidization of the Fund's Emergency Assistance for Natural Disasters to PRGF-Eligible Members. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper provides the semi-annual update on the financing of PRGF and HIPC operations and the subsidization of post-conflict emergency assistance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: PP; PRGF Arrangement; SDR; Subsidization; Subsidy; Sierra Leone